1999
DOI: 10.1248/bpb.22.37
|View full text |Cite
|
Sign up to set email alerts
|

Acceleration of Development of Diabetic Cataract by Hyperlipidemia and Low High-Density Lipoprotein in Rats.

Abstract: Diabetic cataracts are thought to be caused by hyperglycemia associated with disturbed glucose metabolism. Diabetes mellitus often involves abnormal lipid metabolism in addition to abnormal glucose metabolism. To date, however, very few studies have counted hyperlipidemia as a risk factor for diabetic cataracts. The present study was undertaken to determine whether this abnormal lipid metabolism is a risk factor for diabetic cataracts in rats. Cataracts were caused by streptozotocin (STZ) administration in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
13
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(16 citation statements)
references
References 0 publications
3
13
0
Order By: Relevance
“…28 Animal studies indicate that these factors interact to promote cataract development, and modification of one factor may be used to reduce risk from another. 29 Similar to our findings, HTN has also been associated with cataract in other cross-sectional 30 and case-control studies. However, the results are inconsistent 31 and the Blue Mountains Eye Study even reported HTN to be inversely related to nuclear cataract (OR ¼ 0.8).…”
Section: Discussionsupporting
confidence: 92%
“…28 Animal studies indicate that these factors interact to promote cataract development, and modification of one factor may be used to reduce risk from another. 29 Similar to our findings, HTN has also been associated with cataract in other cross-sectional 30 and case-control studies. However, the results are inconsistent 31 and the Blue Mountains Eye Study even reported HTN to be inversely related to nuclear cataract (OR ¼ 0.8).…”
Section: Discussionsupporting
confidence: 92%
“…Other cross-sectional studies also reported that either no association with serum cholesterol levels or higher levels of serum cholesterol in controls [20,21]. One animal study had suggested a possible association between abnormal lipid metabolism and the early onset of diabetic cataracts [22]. Both whole blood glutathione values and erythrocyte superoxide dismutase activities, the indicator of lipid peroxidation concentrations, were significantly lower in the diabetic cataractous patients than those in the senile cataractous group [23].…”
Section: Discussionmentioning
confidence: 97%
“…A strong association was found between low levels of HDL cholesterol and the development of lens opacities of adults of both genders from South Africa [38]. Animal studies have shown acceleration of the development of diabetic cataracts by hyperlipidemia and low HDL in rats [39]. Inflammation and oxidative stress resulting from reduced HDL cholesterol levels could induce cataract formation [28], [40][42].…”
Section: Discussionmentioning
confidence: 99%